APPLICATION OF DRONES IN MODERN GEOSPATIAL CARTOGRAPHY - Khonturaev, Sardorbek (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article discusses the use of unmanned aerial vehicles (UAVs) to create georeferenced maps and 3D models. Particular attention is paid to RTK technology, GNSS solutions, and data post-processing methods. Formulas for calculating coordinates, errors, and coverage density are presented. The effectiveness of using RTK drones in comparison with traditional mapping methods is substantiated.